Manajemen Pengelolaan Wakaf Tunai Di Yayasan Pendidikan Dan Dakwah Islam Wihdatul Ummah Batusangkar - Yulia Fitri (ZAWA: Management of Zakat and Waqf Journal, 2022)
The main problem in this study is in the management of cash waqf management at the Islamic education and da'wah foundation Wihdatul Ummah Batusangkar. The purpose of this discussion is to find out the management of cash waqf management at the Islamic education and da'wah Foundation Wihdatul Ummah Batusangkar. The type of research that the author uses is a type of field research (field research), with qualitative descriptive methods. The data collection technique that the author performs is through interviews and through documentation. The results of this study show that cash waqf management management has not gone well, it is shown from the number of cash waqf collections that continue to decline in each year, and collection is still within the internal scope. In an effort to develop productive waqf, the Islamic education and da'wah foundation Wihdatul Ummah Batusangkar has opened a Qurrata A'yun mart and invested funds in the admission of new students (PMB) in the procurement of clothing. Meanwhile, the inhibiting factor is that the socialization efforts carried out by the nazir regarding cash waqf to the community have not been optimal, limited understanding of the community and inadequate human resources.